1996
DOI: 10.1111/j.1476-5381.1996.tb15586.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of probucol in arteries from normal and hypercholesterolaemic rabbits

Abstract: 1 The effect of probucol on the vascular reactivity of different arteries isolated from rabbits was studied as well as its effects on the development of atherosclerosis in a cholesterol-fed rabbit model. 2 Probucol 1O6-5 x 10-4 M produced a concentration-dependent inhibition of the contractile responses induced by KCl (80 mM), the sequence for the IC50 was: mesenteric artery (5th branch, 4.8+2.6 x 10-5 M) >aorta (8.2+2.3 x l0-M) >femoral artery (>5 x 0-4 M). The response to noradrenaline was: mesenteric artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
2
1
1
Order By: Relevance
“…The time-coursed progressions of atherosclerotic lesions in apoE-deficient and LDLR-deficient mice are histopathologically similar to those observed in humans and other species [15 ± 17]. It has been reported that probucol attenuates lesion development in Watanabe heritable hyperlipidemic (WHHL) rabbits [18 ± 21], cholesterol-fed rabbits [22], and non-human primates fed a high-fat, high-cholesterol diet [23], although the effectiveness of probucol was questioned in some experiments [24,25]. In contrast, more recent data using murine models showed a new aspect of probucol on the development of atherosclerosis.…”
Section: Introductionsupporting
confidence: 56%
“…The time-coursed progressions of atherosclerotic lesions in apoE-deficient and LDLR-deficient mice are histopathologically similar to those observed in humans and other species [15 ± 17]. It has been reported that probucol attenuates lesion development in Watanabe heritable hyperlipidemic (WHHL) rabbits [18 ± 21], cholesterol-fed rabbits [22], and non-human primates fed a high-fat, high-cholesterol diet [23], although the effectiveness of probucol was questioned in some experiments [24,25]. In contrast, more recent data using murine models showed a new aspect of probucol on the development of atherosclerosis.…”
Section: Introductionsupporting
confidence: 56%
“…A previous study showing that probucol suppressed KCl-and norepinephrine-induced Ca 2+ influx [Del Rio et al, 1996] in blood vessels is compatible with our results. In our study, probucol at a concentration of 10 µM was able to suppress the amplitude of I Ca,L in GH 3 cells without altering the I-V relationship of I Ca,L .…”
Section: Discussionsupporting
confidence: 95%
“…-antagonistic properties in smooth muscle [Sgaragli et al, 1993;Del Rio et al, 1996]. However, we were unable to find any effect of probucol on Ca 2+ -activated or voltage-dependent K + currents in GH 3 cells.…”
Section: +contrasting
confidence: 74%
“…Although the exact mechanisms that link diabetes and ROS with MMP expression are not fully understood, additional studies are necessary to further define MMPs as potential therapeutic targets in diabetic blood vessel dysfunction. [170,171,172,173], we could describe changes in subcellular (perinuclear and subplasmalemmal) Ca 2+ distribution in smooth muscle cells from diabetic patients [174] (Fig. 3).…”
Section: Nomentioning
confidence: 98%